Vulnerability Assessment of Reinforced Concrete Building Subjected to Seismic Loads Using Pushover Analysis - Endah Wahyuni; Data Iranata; Heppy Kristijanto (Institut Teknologi Sepuluh Nopember, 2014)
Buildings should be designed to withstand an earthquake based on earthquake planning standard. However, the references used in the regulation could not show building performance to the actual earthquake directly. Therefore, it required an assessment of the existing buildings, in order to evaluate their vulnerability (structural performance level).This study discussed the vulnerability assessment of reinforced concrete buildings from the analysis of the relationship between base shear and displacement, and any failure that occurred.The first step of the evaluation was analyzed the seismic loads with Static Nonlinear (Pushover) Analysis using SAP2000 software. The pushover analysis results showed the level of damage to assessthe building damages. This research was based on SNI 03-1726-2002, Federal Emergency Management Agency (FEMA) 273/356, FEMA 440, and the Applied Technology Council (ATC)-40. Displacement values obtained from Pushover Analysis compared with the field studies. From the pushover analysis, the results obtained the capacity curve showing the relationships between the base shearsand the displacements, reviewed at each elastic conditions, ultimate, plastic and collapse. The numerical results turned out to be closed to the performance level of the structure in the field. Thus the analysis can be used as a reference on an assessment level of performance and behavior of the existing structure as well as the vulnerability of the structure.